Arabidopsis Tetraspanins Are Confined to Discrete Expression Domains and Cell Types in Reproductive Tissues and Form Homo- and Heterodimers When Expressed in Yeast - Boavida, L. C. (2013)
Tetraspanins are evolutionary conserved transmembrane proteins present in all multicellular organisms. In animals, they are known to act as central organizers of membrane complexes and thought to facilitate diverse biological processes, such as cell proliferation, movement, adhesion, and fusion. The genome of Arabidopsis (Arabidopsis thaliana) encodes 17 members of the tetraspanin family; however, little is known about their functions in plant development. Here, we analyzed their phylogeny, protein topology, and domain structure and surveyed their expression and localization patterns in reproductive tissues. We show that, despite their low sequence identity with metazoan tetraspanins, plant tetraspanins display the typical structural topology and most signature features of tetraspanins in other multicellular organisms. Arabidopsis tetraspanins are expressed in diverse tissue domains or cell types in reproductive tissues, and some accumulate at the highest levels in response to pollination in the transmitting tract and stigma, male and female gametophytes and gametes. Arabidopsis tetraspanins are preferentially targeted to the plasma membrane, and they variously associate with specialized membrane domains, in a polarized fashion, to intercellular contacts or plasmodesmata. A membrane-based yeast (Saccharomyces cerevisiae) two-hybrid system established that tetraspanins can physically interact, forming homo- and heterodimer complexes. These results, together with a likely genetic redundancy, suggest that, similar to their metazoan counterparts, plant tetraspanins might be involved in facilitating intercellular communication, whose functions might be determined by the composition of tetraspanin complexes and their binding partners at the cell surface of specific cell types.